An Application of Social Marketing Theory to Develop a Social Marketing Campaign to Address Mental Health Literacy and Help-seeking Behavior among Male College Students - Rita DeBate; Amy Gatto (New Prairie Press, 2021)
Male college students have been observed to have low mental health literacy and help-seeking behaviors. The purpose of this study was to apply social marketing theory to address mental health literacy among male undergraduate students in order to improve both mental health literacy and help-seeking behaviors. The current study employed qualitative methods involving key informant interviews among male undergraduate university students (n = 26). Participants were provided three vignettes representing a male college student presenting with anxiety, depression, or stress during the key informant interviews. The concepts from the key informant interviews were mapped onto the social marketing theory marketing mix (product, price, place, promotion). The social marketing mix identified methods to improve professional help-seeking behaviors (product) among male undergraduate students by reducing stigma, both perceived social stigma and self-stigma, as well as addressing masculine norms (price) in locations where students are comfortable, such as the university health center or the Internet (place), by connecting the physical signs and symptoms (promotion) to mental health concerns. Findings were translated into a targeted and tailored social marketing campaign implemented in male restrooms in the campus recreation center. Social marketing theory is a valuable tool for developing targeted and tailored social marketing programs for mental well-being among college students.